Association Between Posyandu’s Role in Maternal Nutrition Monitoring and Stunting in Puyung - Latifa, Nindy Citra; Nurbaiti, Lina; Hasby, Amelia Ramdani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Stunting is a health issue, particularly in poor nations such as Indonesia. One factor that contributes to stunting is mothers' nutritional status during pregnancy. Integrated Health Posts (Posyandu) monitor pregnant women's nutritional status by assessing mid-upper arm circumference (LILA), hemoglobin (Hb) levels, and maternal compliance with iron supplementation (TTD). The purpose of this study is to examine the association between Posyandu's role in monitoring pregnant women's nutritional status and the prevalence of stunting at the Puyung Community Health Center in Central Lombok Regency. This is an analytical correlation study conducted in a cross-sectional design. The sampling method was stratified random sampling. Data was collected using the KIA Handbook and questionnaires. The chi-square test was utilized while analyzing bivariate data. Of the 90 responders, 8 (8.9%) had low nutritional status during pregnancy, and 49 (54.4%) had stunted toddlers at the Puyung Community Health Center in Central Lombok. The bivariate test using the chi-square method yielded a p-value of 0.791 (p > 0.05), indicating that there is no significant relationship between maternal nutritional status during pregnancy and the incidence of stunting in the working area of Puyung Health Center, Central Lombok Regency. The study concludes that there is no significant association between the involvement of integrated health posts (Posyandu) in monitoring maternal nutritional status during pregnancy and the prevalence of stunting in Puyung Health Center's operational area, Central Lombok Regency.